The Uncertainties of Student Affairs Professionals in the Age of Artificial Intelligence - Owusu, Francisca; Bismark, Wiafe Bimpong (East African Journal of Education Studies, 2024)
The introduction of artificial intelligence (AI) has led to a global revolution across industries and service sectors. AI raises concerns such as job displacement and academic dishonesty. Their duties, involving using different technologies, have led them to incorporate AI technology into their work. This paper delves into the future of the student affairs profession, with a specific focus on the impact of artificial intelligence. The paper analyzes existing literature to identify emerging trends of uncertainties and points out potential opportunities associated with integrating AI into the role of student affairs professionals. This paper explores the nuances of integrating AI into student affairs, including both the opportunities and potential threats. In this paper, it was argued that professionals should identify the aspects of their job that necessitate a personal touch and concentrate their efforts on enhancing human experiences